A Mechanistic Study on the Tautomerism of H-Phosphonates, H-Phosphinates and Secondary Phosphine Oxides - Daniella Vincze; Péter Ábrányi-Balogh; Péter Bagi; György Keglevich (Molecules, 2019)
H-phosphonates, H-phosphinates and secondary phosphine oxides may be preligands, and are important building blocks in the synthesis of pharmaceuticals, pesticides, and P-ligands. The prototropic tautomerism influenced by substituent effects plays an important role in the reactivity of these species. The main goal of our research was to study the tautomerism of the >P(O)H reagents by means of computational investigations applying several DFT methods at different levels. We focused on the effect of implicit solvents, and on explaining the observed trends with physical chemical molecular descriptors. In addition, multiple reaction pathways incorporating three P-molecules were elucidated for the mechanism of the interconversion.